Pengaruh Stereotip Gender Guru PAUD Terhadap Perkembangan Fisik Motorik Dan Sosial Emosional Anak Usia Dini - Churiyah Churiyah; Rachma Hasibuan (Institut Nalanda, 2024)
This study aims to analyze the influence of gender stereotypes held by Early Childhood Education (PAUD) teachers on the physical, motoric and social emotional development of early childhood. Gender stereotypes can influence the way teachers interact with children, which in turn can affect their development in various aspects. The method used in this research is a quantitative method with a survey design. Data was collected through questionnaires distributed to PAUD teachers and direct observation of teacher interactions with children in class. The research results show that teachers' gender stereotypes significantly influence children's physical, motoric and social emotional development. Teachers who hold strong gender stereotypes tend to provide more support and opportunities to children according to traditional gender roles, resulting in an imbalance in the development of physical motor and social emotional skills between boys and girls. This research suggests the need for training for PAUD teachers to be aware of and overcome gender stereotypes, as well as the importance of more inclusive and gender-sensitive educational approaches to support the holistic development of early childhood.